2011
DOI: 10.1089/jpm.2010.0444
|View full text |Cite
|
Sign up to set email alerts
|

Paroxysmal Sympathetic Hyperactivity (Sympathetic Storm) in a Patient with Permanent Vegetative State

Abstract: Paroxysmal sympathetic hyperactivity is a relatively common complication early in the course of traumatic brain injury. Recognition of the clinical presentation of this syndrome is important to palliative and hospice care providers who may be caring for patients with PVS. The treatment of sympathic hyperactivity to reduce potential physical suffering includes medications targeted to the sympathetic nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…It may be less appropriate for paroxysmal symptoms, since it may potentiate hypotension and bradycardia between paroxysms, making titration challenging. 36 However, clonidine patches can be effective in controlling the storms, even late in the course of the patient 40 . Dexmedetomidine has also been reported to be effective in managing PSH in the ICU 41,42 .…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…It may be less appropriate for paroxysmal symptoms, since it may potentiate hypotension and bradycardia between paroxysms, making titration challenging. 36 However, clonidine patches can be effective in controlling the storms, even late in the course of the patient 40 . Dexmedetomidine has also been reported to be effective in managing PSH in the ICU 41,42 .…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…PSH has been reported in conditions other than TBI. These include hypoxic brain injuries, brain tumors, hydrocephalus, and subarachnoid hemorrhages [2]. Although the pathophysiology of PSH is not known, it has been postulated as a result of the disinhibition of the central sympathoexcitatory regions, leading to catecholamine release and a subsequent hyperadrenergic state [6].…”
Section: Discussionmentioning
confidence: 99%
“…Suggested medications include clonidine, dantrolene, lorazepam, morphine sulfate, and nonselective beta-blockers. These may be used individually or in combination [2]. In our patient, a symptom triggered approach was pursued once the diagnosis was established and, eventually, palliation was decided upon by the family.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other medications included dopamine receptor agonists (eg bromocriptine), non-selective beta-blockers (eg propranolol), α2-adrenergic receptor agonists (clonidine), benzodiazepines, muscle relaxants, dopamine (eg levodopa), GABA drugs (eg gabapentin and baclofen), etc. In most cases, they needed to be taken together (12,14,16,17). Small sample studies suggested that HBOT can serve as an auxiliary means of medication (18).…”
Section: Paroxysmal Sympathetic Hyperactivity With Tuberculous Meningmentioning
confidence: 99%